2022
DOI: 10.3389/fevo.2022.1041322
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in the home range of the subterranean rodent Myospalax baileyi

Abstract: As ecosystem engineers, subterranean rodents excavate and inhabit burrow systems. However, the changes in their use of underground space are poorly recorded. There is conflicting evidence about whether the burrow systems of subterranean rodents, once established, are relatively stable as a result of the high energy costs of digging. We monitored the size of the home ranges of the plateau zokor (Myospalax baileyi) during different stages of its life cycle to show whether mating behavior and the characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Zokors are predominantly subterranean, do not hibernate and are territorial solitary animals (Makh mutov 1983;Bazhenov 2017;Zhou et al 2022). Modern populations of M. myospalax inhabit open landscapes with sufficient underground phytomass and a moderate climatic regime, which corresponds to meadow biotopes (Galkina and Nadeyev 1980;Makhmutov 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zokors are predominantly subterranean, do not hibernate and are territorial solitary animals (Makh mutov 1983;Bazhenov 2017;Zhou et al 2022). Modern populations of M. myospalax inhabit open landscapes with sufficient underground phytomass and a moderate climatic regime, which corresponds to meadow biotopes (Galkina and Nadeyev 1980;Makhmutov 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Modern populations of M. myospalax inhabit open landscapes with sufficient underground phytomass and a moderate climatic regime, which corresponds to meadow biotopes (Galkina and Nadeyev 1980;Makhmutov 1983). The results of studies of habi tats of individuals plateau zokors Eospalax baileyi (Thomas, 1911) (family Myospalacidae) revealed that the size of their home habitat (burrow length) negatively correlates with the level of subterranean biomass (Zhou et al 2022). This pattern is proba bly true for the Siberian zokor.…”
Section: Discussionmentioning
confidence: 99%